Downsizing and its effects on the turnover intention of surviving employees in Malaysia - Liew, Ee Yin (2012)
Downsizing is defined as a purposeful reduction in the size of organization’s workforce. Organizational downsizing has increasingly occurred throughout the workplace over the past decades of years. Prior research has shown that downsizing can have profound effects on survivors’ (i.e. those who remain employed subsequent to downsizing) behaviors. The purpose of this study is to examine the effects of organizational downsizing on surviving employees’ turnover intention. The sample of the study was the survivors of organizational downsizing from all levels of employees. The respondents were from organizations which were involved in employee retrenchment during the year 2009. These organizations are located in Selangor, Penang and Johore. Job insecurity and shock were found significantly and positively affects the intention to leave an organization of the surviving employees. Job embeddedness moderates the relationship between job insecurity and turnover intention, specifically the sacrifice-community and sacrifice-organization sub-dimensions of job embeddedness. In terms of moderating roles of employees’ demographic variables, only age was found to have moderating effects on the relationship between job insecurity and turnover intention. The implications of this study from both theoretical and managerial perspective were discussed. Managers within organizations should plan for downsizing as an effort to reduce shocks for the surviving employees. Resources should be focused on the human resource practices which foster employees’ job embeddedness by increasing their links, fits and sacrifices with the organization and community. Limitations and directions for future research are also discussed.